2013
DOI: 10.9745/ghsp-d-12-00051
|View full text |Cite
|
Sign up to set email alerts
|

Client-centered counseling improves client satisfaction with family planning visits: evidence from Irbid, Jordan

Abstract: In Irbid, Jordan, a combination of community outreach, using home visits, plays, women's groups, and religious leaders, and improved client-provider counseling based on the “Consult and Choose” approach increased family planning demand and client satisfaction. Service statistic trends suggest increased contraceptive use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 16 publications
8
45
1
Order By: Relevance
“…One study indicated a 20% increase in patient satisfaction with family planning services with each additional counselling protocol step. 5 Another study previously investigated the effect of involving men in counselling; however, the content of the sessions was not evaluated. 11 Finally, various other studies have analysed general family planning services rather than focusing specifically on counselling.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…One study indicated a 20% increase in patient satisfaction with family planning services with each additional counselling protocol step. 5 Another study previously investigated the effect of involving men in counselling; however, the content of the sessions was not evaluated. 11 Finally, various other studies have analysed general family planning services rather than focusing specifically on counselling.…”
mentioning
confidence: 99%
“…4 Another national study in Jordan has indicated that family planning services are often influenced by the personal beliefs of the providers; for example, most providers emphasised the importance of a large family and recommended short-term contraceptive methods for women with fewer children, refusing to suggest semipermanent approaches like an intrauterine device. 5 Religious and social beliefs also influenced family planning recommendations, with some providers expressing preference for a male child. 5 According to the 2015-2019 strategic plan of the MOH, the strengthening of reproductive health services is a top priority.…”
mentioning
confidence: 99%
See 3 more Smart Citations